Acute Stroke Care in Mexico City: The Hospital Phase of a Stroke Surveillance Study - Emmanuel Aguilar-Salas; Guadalupe Rodríguez-Aquino; Katya García-Domínguez; Catalina Garfias-Guzmán; Erika Hernández-Camarillo; Nayeli Oropeza-Bustos; Rubí Arguelles-Castro; Ameyalli Mitre-Salazar; Gloria García-Torres; Marco Reynoso-Marenco; Eduardo Morales-Andrade; Luis Gervacio-Blanco; et al. (Brain Sciences, 2022)
Background: Acute stroke care has greatly improved in recent decades. However, the increasing stroke mortality in low-to-middle income countries suggests that progress has not been reached completely by these populations. Here we present the analysis of the hospital phase of the first population-based stroke surveillance study. Methods: A daily hospital surveillance method was used to identify adult patients with acute stroke during 18 months in six hospitals. We abstracted data on demographics, vascular risk factors, neuroimaging-confirmed stroke types, and clinical data. Results: A total of 1361 adults with acute stroke were identified (mean age 69.2 years; 52% women) with transient ischemic attack (5.5%), acute ischemic stroke (68.6%), intracerebral hemorrhage (23.1%), cerebral venous thrombosis (0.2%), and undetermined stroke (2.6%). The main risk factors were hypertension (80.7%) and diabetes mellitus (47.6%). The usage rate of thrombolysis was 3.6%, in spite of the fact that 37.2% of acute ischemic stroke patients arrived in <4.5 h. The 30-day case fatality rate was 32.6%, higher in hemorrhagic than ischemic stroke. Conclusion: We identified limitations in acute stroke care in the Mexico City, including neuroimaging availability and thrombolysis usage. The door-to-door phase will help to depict the acute stroke burden in Mexico.